Key Drivers of Digital Platform Usage Intention Among Physical Banking Users in Ecuador - Priscila, Vallejo Bojorque Adriana; Judith, Cavazos Arroyo; Gliceria , Gómez Ceballos (Journal of Ecohumanism, 2025)
The objective of this research was to determine the influence and intensity of perceived risks associated with electronic banking usage in an integrated manner and to explain the effect of different types of perceived risk on attitudes toward online banking, as well as their subsequent impact on the intention to use digital platforms, which constitutes the study’s fundamental contribution. To achieve this, the construction of "perceived risk" was analyzed, drawing upon several theoretical frameworks, including the Theory of Reasoned Action (TRA), the Theory of Planned Behavior (TPB), and other related models. The sample consisted of 938 users from private banking institutions in Cuenca, Ecuador, and structural equation modeling was employed for the analysis. The findings revealed that privacy, performance, security, time, and psychological risks have a direct impact on attitudes toward online banking. In contrast, financial risk was found not to have a direct effect on such attitudes, a result consistent with the findings of others researches. Furthermore, it was confirmed that attitudes toward online banking are a decisive factor in determining the intention to use this service, providing valuable insights and guidelines for various stakeholders in the sector.